Facile synthesis of three-dimensional Ni3Sn2S2 as a novel battery-type electrode material for high-performance supercapacitors. (10th November 2021) - Ma, Lin; Hu, Rui; Kang, Chenxia; Fu, Likang; Chen, Yucheng; Liu, Huijun; Liu, Qiming
Highlights: Novel Ni3 Sn2 S2 nanoflowers were prepared by one-pot hydrothermal and ion corrosion. The optimized Ni3 Sn2 S2 displays rational 3D flower-like composite structure. Ni3 Sn2 S2 /Ni foam is firstly used as an electrode material for supercapacitor. The fabricated asymmetric device shows ultrahigh energy density of ∼ 5.22 mWh cm −3 . Abstract: Binary system sulfides hold tremendous potential for the manufacture of high-performance supercapacitors because of their rich transition states. Herein, three-dimensional Ni3 Sn2 S2 flower-like materials on Ni foam are ingeniously created via a simple one-pot hydrothermal and ion corrosion for employing as the electrode material in supercapacitors for the first time. According to the morphology in different reaction time, the growth mechanism of the flower-like Ni3 Sn2 S2 is further proposed. The morphology of as-prepared optimal sample indicates that the space of material is fully utilized to form a favorable compound structure with interconnected and uniformly branched nanosheets on the surface of polyhedrons. Electrochemical measurement reveals that Ni3 Sn2 S2 has a high area-specific capacitance of 0.67 mAh cm −2 at a current density of 2 mA cm −2 . Impressively, the hybrid supercapacitor assembled with Ni3 Sn2 S2 /Ni foam cathode and commercial activated carbon anode delivers a maximum energy density of 4.65 mWh cm −3 at a power density of 29.64 mW cm −3 . Two devices in series can lit up 22 blue Light-Emitting Diodes more than 130 min. On the strength of outstanding electrochemical performances, Ni3 Sn2 S2 is a novel and promising electrode material for supercapacitor.